Respuesta :
[tex]\left\{\begin{array}{ccc}3x+2y=-21\\x-3y=4&|Add\ 3y\ to\ both\ sides\end{array}\right\\\\\left\{\begin{array}{ccc}3x+2y=-21\\x=4+3y\end{array}\right\\\\substitute\ into\ the\ first\ equation\\\\3(4+3y)+2y=-21\\\\\boxed{Answer:\ 3(3y+4)+2y=-21} [/tex]
Answer:
3(3y+4)+2y=-21
Step-by-step explanation:
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the second equation is substituted into the first equation.
3x + 2y = -21
x - 3y = 4
Solve the second equation for x
x-3y= 4
Add 3y on both sides
x= 4+ 3y
Now replace 4+3y for x in first equation
3(4+3y) +2y= -21
3(3y+4)+2y=-21